The Composition and Visual Transformation of Huxiang Cultural Factor (Asian Journal of Social Science Studies, 2022)
There is a complementary relationship between Huxiang cultural resources and design. The effective combination of the two can better show the visual transformation effect and cultural connotation of the design. At the same time, it can enhance the value and connotation of the design object, so as to realize the development and protection of culture. Therefore, the visual transformation, integration and development of Huxiang culture have a broader prospect, which is worth further study. This paper analyzes the composition of Huxiang culture factors, and carries out the transformation of modern visual design. It also elaborates the identification and extraction, design and transformation of Huxiang cultural factors, hoping to provide positive exploration and thinking for the protection and inheritance of our traditional culture.